Keberkesanan Sistem Pengurusan Harta Secara Pendekatan Analisa Kewangan Dan Persepsi Penyewa - Md Yusof, Haspalela (1995)
This dissertation is prepared to ascertain the effectiveneof the asset or property Management systems that is currently practice in the local property industry. The concept is to manage owners' property and maintain physically to a satisfactory condition, besides maximising return and reducing operational and maintenance cost. Thus, promoting and projecting an ideal corporate image that could enhances the property value.